2020
DOI: 10.17507/jltr.1106.23
|View full text |Cite
|
Sign up to set email alerts
|

Componential Analysis of ‘Gbá’ Verbal Complex and Its Relevance in Second Language Teaching

Abstract: This work examines the componential analysis of the gbá verbal complex in Igbo. It investigates the complex verb gbá in order to find out the basic components of the verb in Igbo thereby arriving at its lexical meaning. The paper adopts the theory of componential analysis for the analysis of data. The data used for the study were elicited through informal interview and the researchers’ intuitive knowledge as native speakers. The study found out that ‘gbá’ is a verb of movement or motion which results into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The lexical meaning of a complex verb Gbá in Igbo provided more insight to this study. Nwachi, Babarinde, Nwachi, Babarinde, & Ahamefula (2020) concluded that Gbá was a verb of movement or motion resulting in the change of position. The data were elicited through interviews.…”
Section: 1mentioning
confidence: 99%
“…The lexical meaning of a complex verb Gbá in Igbo provided more insight to this study. Nwachi, Babarinde, Nwachi, Babarinde, & Ahamefula (2020) concluded that Gbá was a verb of movement or motion resulting in the change of position. The data were elicited through interviews.…”
Section: 1mentioning
confidence: 99%